Tutors’ Paradox on ChatGPT Assistance in English as a Foreign Language Distance Learning Environments - Hadianti, Siti (Journal of English Language and Education, 2026)
Distance learning has been one way to provide accessible education across Indonesia's vast geographical area and dense population. However, the emergence of artificial intelligence (AI), particularly ChatGPT with its free access, may have disrupted the reciprocal learning process between the tutor as an online lecturer and the students. This research involved 42 active tutors from the English Education Department at Universitas Terbuka (UT), the only open and distance learning university in Indonesia. With more than 650.000 students, the university relies heavily on online tutorials (Tuton), in which student-tutor interaction has been significantly influenced by the presence of ChatGPT. By gathering data through open and closed-ended questionnaires and analyzing it using a mixed-methods approach, the study revealed a contrast in perspectives among tutors, which the researchers refer to as a ‘paradox of perspective’. This condition presents with the fact that the tutors were struggling to identify the AI used, even though they seemed to show they could adjust to the situation. They also questioning the authenticity of students work yet unable to detect the ChatGPT intervention.  The finding might imply an urge for a distance learning institution like UT to address the issue. There are two major recommendations from the tutor by having a guideline for ChatGPT usage by the students and training for the tutor in dealing with the AI disruption.